Physical mechanism behind enhanced photoelectrochemical and photocatalytic properties of superhydrophilic assemblies of 3D-TiO2 microspheres with arrays of oriented, single-crystalline TiO2 nanowires as building blocks deposited on fluorine-doped tin oxid - Sadhu, Subha; Gupta, Preeti; Poddar, Pankaj (ACS Applied Materials & Interfaces, 2017)
In comparison to the one-dimensional (1D) semiconductor nanostructures, the hierarchical, three-dimensional (3D) microstructures, composed of the arrays of 1D nanostructures as building blocks, show quite unique physicochemical properties due to efficient photon capture and enhanced surface to volume ratio, which aid in advancing the performance of various optoelectronic devices. In this contribution, we report the fabrication of surfactant-free, radially assembled, 3D titania (rutile-phase) microsphere arrays (3D-TMSAs) composed of bundles of single-crystalline titania nanowires (NWs) directly on fluorine-doped conducting oxide (FTO) substrates with tunable architecture. The effects of growth parameters on the morphology of the 3D-TMSAs have been studied thoroughly. The 3D-TMSAs grown on the FTO-substrate showed superior photon-harvesting owing to the increase in light-scattering. The photocatalytic and photon to electron conversion efficiency of dye sensitized solar cells (DSSC), where the optimized 3D-TMSAs were used as an anode, showed around 44% increase in the photoconversion efficiency compared to that of Degussa P-25 as a result of the synergistic effect of higher surface area and enhanced photon scattering probability. The TMSA film showed superhydrophilicity without any prior UV irradiation. In addition, the presence of bundles of almost parallel NWs led to the formation of arrays of microcapacitors, which showed stable dielectric performance. The fabrication of single-crystalline, oriented, self-assembled TMSAs with bundles of titania nanowires as their building blocks deposited on transparent conducting oxide (TCO) substrates has vast potential in the area of photoelectrochemical research.